Beyond dopamine: functional MRI predictors of responsiveness to cognitive behaviour therapy for psychosis - Kumari, Veena; Antonova, Elena; Fannon, Dominic; Peters, Emmanuelle R.; Ffytche, Dominic H.; Premkumar, Preethi; Raveendran, Vinodkumar; Andrew, Christopher; Johns, Louise C.; McGuire, Philip A.; Williams, Steven C.; Kuipers, Elizabeth (Frontiers in Behavioral Neuroscience, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Despite the favourable effects of antipsychotics on positive symptoms of schizophrenia, many patients continue to suffer from distressing symptoms. Additional benefi ts of cognitive behavior therapy for psychosis (CBTp) have been reported for approximately 50% of such patients. Given the role of left hemisphere-based language processes in responsiveness to CBT for depression, and language pathway abnormalities in psychosis, this study examined whether pre-therapy brain activity during a verbal monitoring task predicts CBTp responsiveness in schizophrenia. Fifty-two outpatients, stable on antipsychotics with at least one persistent distressing positive symptom and wishing to receive CBTp adjunctive to their treatment-as-usual, and 20 healthy participants underwent fMRI during monitoring of self- and externally-generated (normal and distorted) speech. Subsequently, 26 patients received CBTp for 6-8 months adjunctive to their treatment-as-usual (CBTp + TAU, 20 completers), and 26 continued with their treatment-as-usual (TAU-alone, 18 completers). Symptoms were assessed (blindly) at entry and follow-up. The CBTp + TAU and TAU-alone groups had comparable demographic characteristics, performance and baseline symptoms. Only the CBTp + TAU group showed improved symptoms at follow-up. CBTp responsiveness was associated with (i) greater left inferior frontal gyrus (IFG) activity during accurate monitoring, especially of own voice, (ii) less inferior parietal deactivation with own, relative to others', voice, and (iii) less medial prefrontal deactivation and greater thalamic and precuneus activation during monitoring of distorted, relative to undistorted, voices. CBTp + TAU patients, on average, displayed left IFG and thalamic hypo-activation (